2013
DOI: 10.1111/cei.12034
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-bound interleukin-21 and CD137 ligand induce functional human natural killer cells from peripheral blood mononuclear cells through STAT-3 activation

Abstract: SummaryNatural killer (NK) cell adoptive transfer is a promising approach for cancer immunotherapy; however, its development has been hindered by the lack of efficient methods to produce large numbers of functional NK cells. In this study, we engineered the leukaemia cell line K562 to express CD137 ligand (CD137L) and membrane-bound interleukin (mbIL)-21 on the cell surface, and used these cells to expand NK cells from the peripheral blood mononuclear cells. We found that purity of the NK cells (CD3 -CD56 + /C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 20 publications
(24 reference statements)
0
46
0
1
Order By: Relevance
“…18 However, we also observed that the level of NKG2D expression was significantly greater in NK cells activated with IL-21 ( Figure 1A). To determine whether this was caused by increased transcription of NKG2D, or of its signaling coreceptors DAP10 and DAP12, we assessed the messenger mRNA (mRNA) transcripts for these molecules on freshly-purified human NK cells compared with those expanded with mbIL15 or mbIL21.…”
Section: Il-21 Signaling In Nk Cells Elicits a Greater Increase In Nkmentioning
confidence: 64%
“…18 However, we also observed that the level of NKG2D expression was significantly greater in NK cells activated with IL-21 ( Figure 1A). To determine whether this was caused by increased transcription of NKG2D, or of its signaling coreceptors DAP10 and DAP12, we assessed the messenger mRNA (mRNA) transcripts for these molecules on freshly-purified human NK cells compared with those expanded with mbIL15 or mbIL21.…”
Section: Il-21 Signaling In Nk Cells Elicits a Greater Increase In Nkmentioning
confidence: 64%
“…Like T cells, human and murine NK cells express 4-1BB after activation which can interact with the ligand (4-1BBL) or anti-CD137 antibodies and transduce intracellular signals [12,13]. While some studies showed negative impact of CD137 signal on cytotoxic activities or cytokine production by human or mice NK cells [13][14][15], others could demonstrate the enhancement of those activities [16][17][18]. It means that more investigations are needed to resolve the controversies about the role of 4-1BB costimulation for NK cells' function.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we selected a three-week stimulation cycle based on previous studies using similar cytokines to stimulate NK cells (14,15,30,39), and the cytotoxicity of the expanded NK cells was reported to peak after 3-5 weeks, followed by a decline, although with continuously growing numbers of NK cells (30). Thus, the differences in experimental conditions between the present study and previous reports suggest that it is worthwhile to examine the expansion and killing activity of NK cell through prolonged stimulation and increasing stimulation times.…”
Section: Discussionmentioning
confidence: 99%
“…IL-21, a secreted protein, mediates the proliferation, differentiation and antitumorigenicity of cells via binding to a composite receptor comprising the private receptor IL-21R, which is also expressed on a variety of B, T, NK cell lines, and the common receptor γ-chain, which is also shared by IL-2, IL-4, IL-7, IL-9, IL-13 and IL-15 (26)(27)(28)(29). Wang et al used these two receptor molecules, which were expressed on the feeder cells, to stimulate the expansion of NK cells and achieved significant cell expansion (30). However, a disadvantage of this method is the effective removal of the feeder cells from the activated NK cells.…”
Section: Introductionmentioning
confidence: 99%